Parental Preferences in Children's Menu Provision at Home: An Exploratory Study in West Sumatra - Afnida, Mutia; Sari, Widia Kemala; Arnez, Gaby; Sari, Resti Elma; Trisasmita, Laksmi (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Indonesia continues to face significant challenges in achieving optimal nutrition, as malnutrition persists despite advancements in the health sector. This study explores how parents in West Sumatra make decisions about their children's meals, focusing specifically on their understanding of stunting and the role of dietary variety. The goal is to assess how parental awareness of stunting affects their choices in providing balanced, nutritious meals for their children. The study collected data from 387 parents using a structured questionnaire, analyzed through descriptive and correlational methods. Results showed that rice is the primary staple, consumed an average of 2.78 times per day. Although animal protein sources like fish and eggs are commonly included, vegetable and fruit consumption remain below recommended levels. A weak but positive correlation was identified between parental knowledge and food variety, especially regarding fruits and vegetables. However, this relationship was generally weak (ρ < 0.2), likely shaped by additional factors like household income and food access. The research also uncovered notable variations in parental knowledge depending on socioeconomic status, with higher-income families demonstrating greater awareness of stunting. These outcomes imply that while nutrition education is important, it must be paired with strategies that address broader structural challenges such as affordability and food availability. Further studies using longitudinal or qualitative methods are recommended to better understand the behaviors that influence dietary choices and to inform more effective nutrition policies.